JARANAN CAMPURSARI ART IN ANGSANA VILLAGE AS AN IPS LEARNING RESOURCE - Murtono, Riky (JURNAL SOCIUS, 2024)
Jaranan Art, as part of a folk art tradition dating back to the era of kingdoms, continues to evolve and be preserved by local communities. One enduring form of this art is Jaranan Campursari Singo Budoyo Sakti, originating from Angsana District, Tanah Bumbu Regency. This study aims to describe the presentation form of Jaranan Campursari Singo Budoyo Sakti and to explore its functions within the local community. The research employs a qualitative descriptive method, with data collection techniques including observation, interviews, and documentation, such as notes, photos, and videos supporting the findings. The results reveal that Jaranan Campursari Singo Budoyo Sakti was first established in 2013 by Suparlan, with the assistance of other local artists. This art form serves not only as a medium of entertainment but also as a means of preserving Javanese culture, creating employment opportunities for artists and vendors, and providing income for the surrounding community. It has been well-received and recognized by both the local community and government, as evidenced by high demand for performances at various events such as anniversaries, circumcisions, and weddings. These findings are expected to contribute to efforts to preserve local culture and to enhance understanding of the role of art in the socio-economic life of the community.